Flexible retirement – a model for the future? : lessons from Sweden, Norway and Finland - Vidlund, Mikael; Eläketurvakeskus (Eläketurvakeskuksen raportteja, ISSN 1798-7490, 2017)
Tiivistelmä.
Keywords: eläkkeelle siirtyminen; vanhuuseläke; eläkejärjestelmät; eläkeikä; työ; eläkkeet; yhdistäminen; työura; Ruotsi; Norja; Suomi